Luminescent Glass‐Ceramics Based on Nanoparticles of BaxRE1‐xF2+x and PbxRE1‐xF2+x Solid Solutions into Fluoroborate. Issue 3 (3rd January 2018) - Petrova, Olga; Sevostjanova, Tatjana; Khomyakov, Andrew; Avetissov, Igor
Abstract : Lead‐barium fluoroborate glasses doped with RE are synthesized. Using the heat‐treatment (HT) glass‐ceramics in which RE 3+ (Eu 3+ or Er 3+ ) ions are building into fluoride crystalline nanoparticles homogeneously distributed in the borate glass matrix are made. The changes in the structural and optical properties of the glass‐ceramics comparatively to initial glasses and polycrystalline fluoride containing Pb, Ba, and RE are revealed by X‐ray diffraction and luminescence spectroscopy of RE ions. Abstract : Eu‐ and Er‐doped glass‐ceramics with a cubic crystalline phase are obtained in lead‐barium fluoroborate systems. The glass‐ceramics are transparent in visible and near IR regions. Photoluminescence (including the anti‐Stokes photoluminescence for Er 3+ ) show that Eu 3+ and Er 3+ ions efficiently intercalate into cubic fluoride crystalline nanoparticles and homogeneously distribute in the borate glass matrix.